Kajian Aktivitas Antioksidan Ekstrak Air dan Minyak Buah Tomat (Solanum lycopersicum L.) - Yuliet, Yuliet (Media Eksakta, 2011)
Tomato (Solanum lycopersicum L.) represent an edible fruit which is easily available and known as a source of antioxidant. This research was aimed to test the antioxidant activity of tomato extract in olive oil and water. Antioxidant activity was determined using superoxide dismutase (SOD) and lipid peroxidation (LPO) activity test, ex vivo in Swiss Webster male mice. Result showed that olive oil tomato extract increased significantly (p<0.01) superoxide dismutase (SOD) activity and inhibited lipid peroxidation. The highest activity against superoxide dismutase (SOD) activity (0.85%) and inhibited lipid peroxidation in liver (74.67 %) was given by tomato extract in olive oil at 0.075 mL/kg bw (p<0.01). The highest inhibition of lipid peroxidation in kidney was given by tomato extract in water at dose of 150 mg/kg bw (20.27 %, p<0.01).